Analysis of nutrient resorption efficiency and homeostasis of four tree species in Kanas natural forest, Xinjiang, China - Bagedeng,; Xia, Guozhu; Lin, Tao; Xu, Zhonglin; Wang, Yao (Frontiers in Ecology and Evolution, 2022)
To explore the differences in stoichiometric homeostasis and resorption efficiency of nitrogen (NRE) and phosphorus (PRE) of tree species in Kanas natural forest. We selected four primary tree species: Larix sibirica (LS), Picea obovate (PO), Pinus sibirica (PS), and Betula pendula (BP) and measured concentrations of carbon (C), nitrogen(N) and phosphorus(P) in fresh leaves, leaf litter and soil. Our findings showed that compared to deciduous species (LS, BP), evergreen species (PO, PS) had higher fresh leaves C concentration and C: N ratio. As opposed to evergreen plants, deciduous species have higher levels of fresh leaves N concentration, while the P concentration and C: P did not exhibit such a pattern. Mass-based NRE and PRE averaged 52.55% and 49.16%, respectively, with significant difference among life forms in NRE but no varied in PRE. NRE increased with N concentration in fresh leaves of BP, PO and LS, NRE decreased with N concentration in leaf litter of all specie; PRE increased with P concentration in fresh leaves of all specie, PRE decreased with P concentration in leaf litter of LS, PO and PS. Only NRE of BP and PS and PRE of PS showed significant relationship with soil N and P concentration, respectively. Neither NRE nor PRE was insignificantly related to mean annual temperature (MAT) for all species. N concentration of all species showed strict homeostasis corresponding to their being limited by N element. Only the P concentration of PS and PO and N: P ratio of PS varied with corresponding traits in soil.